1987
DOI: 10.1159/000153677
|View full text |Cite
|
Sign up to set email alerts
|

E<sup>h</sup><sub>1</sub>, a New Allele at Cholinesterase Locus 1

Abstract: Unusual inhibition characteristics in two unrelated suxamethonium-sensitive individuals were indicative of a new allele, Eh1, segregating with the Ea1gene. Family studies substantiate this hypothesis and three new genotypes are recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A new variation was discovered in 1987 by Whittaker & Britten [101] who had set up the Cholinesterase Research Unit at the Hammersmith Hospital in West London and thus bears the label H. Although this gene is very rare, it is associated with a drastic reduction in cholinesterase activity to the level one would expect with a silent gene.…”
Section: Inherited Variationsmentioning
confidence: 99%
“…A new variation was discovered in 1987 by Whittaker & Britten [101] who had set up the Cholinesterase Research Unit at the Hammersmith Hospital in West London and thus bears the label H. Although this gene is very rare, it is associated with a drastic reduction in cholinesterase activity to the level one would expect with a silent gene.…”
Section: Inherited Variationsmentioning
confidence: 99%
“…The lengths of the products are indicated. tant) (A), the fluoride-resistant (F), the silent (S) and the three quantitative, K, J and H, variants [5][6][7], The increasing number of pos sible genotypes has complicated the identifi cation of the different genotypes using only biochemical analyses, including inhibition tests [8 -13]. One of the new quantitative vari ants, the K variant, was first recognized by Rubinstein et al [6], In 1992, Bartels et al [14] determined the amino acid composition of this variant.…”
mentioning
confidence: 99%
“…The three siblings, III 2 4 have low total activities and we wished to determine what allele they had inherited from their mother. Whittaker 9 has reported that 'the E.h allele appears to be associated with a much more drastic reduction in enzymic activity (than Ell and Elk) such as that round in the silent genes'. The presence of the E,h allele was therefore considered very unlikely.…”
Section: Discussionmentioning
confidence: 99%